FORMAÇÃO DOCENTE E ENSINO SUPERIOR A DISTÂNCIA: TRANSIÇÃO PARADIGMÁTICA E OS IMPACTOS E CONTRIBUIÇÕES DAS TECNOLOGIAS DE INFORMAÇÃO E COMUNICAÇÃO - Cardoso, Ana Lucia (2010)
The 21st century has brought deep changes in the organization of societies and consequently in the labor world in the educational field. The exponential growth of the communication dynamics in the societies enables the overall multiplication of world views, the technology is a changing agent and the technological innovations and it may result in a revolutionary educational paradigm break. Against the deadlocks of a globalized world, in constant cultural mutations, new mediation possibilities arise, generating different perspectives to the educative processes with the introduction of the Information and Communication Technologies (ICTs) and Distance Education (DE). That s why, the teaching background is researched in an effort to analyze the impacts and the contributions that such technologies bring to this field, especially in the Pedagogy course, considering an experience in DE and its relation with the course in the modality in attendance from the so-called guidance of the Institutional Pedagogical Project (IPP) in the researched institution. It was relevant to notice throughout the bibliographical research and the field study that both modalities are supported by the education conception that is underlying and that guides the theoretical-methodological choices adopted by the institution in its IPP. Distance education enables the construction of a learning environment, mediated by the ICTs and new comprehension about the teaching and learning process. The teaching background in this modality must be articulated with the educative process and have the conception of someone being able to establish new ways of expression and knowledge as a foundation to work in a future education. Therefore, it s necessary to think about the intention of your background, in order to enable a critical pedagogical view in an attempt to intervene the educational development as an intellectual transformer.(AU)